PERFORMANCE ANALYSIS OF QUALITY OF SERVICE AND ENERGY EFFICIENT AWARE (QEEA) SCHEDULING ALGORITHM FOR LONG TERM EVOLUTION (LTE) - NURULANIS M. YUSOFF; DARMAWATY MOHD ALI; AZLINA IDRIS (Journal of Engineering Science and Technology, 2018)
The growing demands for wireless communication services pose new challenges in the coming generation of cellular networks design. In Third Generation Partnership Project (3GPP) Long Term Evolution (LTE) networks, ever-higher data rate and energy efficiency are required to meet the increasing demands in cellular traffic. This paper proposed an efficient algorithm, namely, the Quality of Service and Energy Efficient Aware (QEEA) to improve energy efficiency (EE) and also maximizing the throughput by using minimum power of 43 dBm (20 W) according to the 3GPP LTE specifications in order to achieve green communication. The QEEA algorithm is compared to the conventional scheduling algorithms, namely, the Channel and Quality of Service (QoS) Aware (CQA), Priority Set Scheduler (PSS), and Proportional Fair (PF) based on the performance metrics of throughput, delay, packet loss ratio (PLR), energy consumption rate (ECR), and EE for the voice over IP (VoIP), video and File Transfer Protocol (FTP) applications. The results show that the QEEA algorithm outperformed the other algorithms as it could achieve up to 18% of maximum throughput, 27% reduction in ECR and also 36% improvement in EE. Thus, it can be concluded that QEEA algorithm is the most energy efficient algorithm for VoIP, video and FTP applications.